KRITERIA PENENTUAN PELAKU KEJAHATAN MENJADI JUSTICE COLLABORATOR - Anastacia Gracella Hartanto, (2024)
Lack of strengthening the role and authority of the Witness and Victim Protection Agency (LPSK) in establishing clearer guidelines regarding granting justice collaborator status as well as lack of coordination between LPSK and other law enforcers in providing justice in the form of legal protection for justice collaborators. This research aims to determine the appropriate criteria for criminals who will become justice collaborators and strengthen the role and authority of the LPSK so that it can provide legal protection to reveal material truths. This research approach uses a statutory approach, a conceptual approach, and a comparative approach. The results of this research found that the terms and conditions for becoming a justice collaborator are divided into 2 Indonesian laws and regulations, namely in Number 9 SEMA No. 04 of 2011 and Article 28 paragraphs (1) and (2) of Law Number 31 of 2014 concerning Witness and Victim Protection Institutions. However, in its implementation, transparency and accountability are required in the preparation of specific guidelines for procedures for determining justice collaborator status, as well as cooperation between law enforcement agencies and LPSK regarding the characteristics and needs of justice collaborators to provide emotional and psychological support during the reporting and trial process. form of legal protection for justice collaborators. This research aims to determine the appropriate criteria for criminals who will become justice collaborators and strengthen the role and authority of the LPSK so that it can provide legal protection to reveal material truths. This research approach uses a statutory approach, a conceptual approach, and a comparative approach. The results of this research found that the terms and conditions for becoming a justice collaborator are divided into 2 Indonesian laws and regulations, namely in Number 9 SEMA No. 04 of 2011 and Article 28 paragraphs (1) and (2) of Law Number 31 of 2014 concerning Witness and Victim Protection Institutions. However, in its implementation, transparency and accountability are required in the preparation of specific guidelines for procedures for determining justice collaborator status, as well as cooperation between law enforcement agencies and LPSK regarding the characteristics and needs of justice collaborators to provide emotional and psychological support during the reporting and trial process